SISTEM INFORMASI BOOKING ANTRIAN BENGKEL MOBIL BERBASIS WEBSITE MENGGUNAKAN METODE RAD (RAPID APPLICATION DEVELOPMENT) DI SMK MUHAMMADIYAH KAWALI - Johana, Rahman; Dwicahya Supriatman, Rian; Maulana, Haisyam (Fakultas Teknik Jurusan Sistem Informasi Universitas Galuh, 2025)
The car workshop queue management system at SMK Muhammadiyah Kawali still relies on inefficient manual processes, often leading to customer congestion, long wait times, and the risk of errors in data recording, thus reducing customer satisfaction and hindering operational effectiveness. Therefore, this research aims to design and build a Website-Based Car Workshop Queue Booking Information System to make it easier for customers to book queues online, improve operational efficiency, and reduce waiting times. The development method used is Rapid Application Development (RAD) to accelerate the development cycle. In its implementation, this system was built using PHP for the back-end, XAMPP as the local server, and MySQL as the database management system to store all queue, service, user, and payment data. With this system in place, it is hoped that the queue booking process will become more structured, thereby improving the quality of workshop services at SMK Muhammadiyah Kawali.